Development of E-module on Classification Game (SIGAME) as Student Learning Resource - Aroyandini, Elvara Norma; Firanti, Annisa (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2026)
This study aims to develop an e-module integrated into the educational game named Classification Game (SIGAME) and to analyze validation results from experts and practitioners. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the stages of Analysis, Design, and Development. The final product was an e-module on living things classification for seventh-grade students, designed as a component of the educational game. Research instruments included needs analysis questionnaires, validation guidelines, and product assessment sheets. The data were analyzed descriptively through both qualitative feedback and quantitative scoring from validators. Findings revealed that the e-module contained complete components such as interactive materials, exercises, answer keys, and summaries. Subject matter experts rated the module as excellent in terms of language, presentation, and content accuracy, although the scope of material remained limited. Media experts evaluated graphical design, interactivity, and layout as highly suitable for junior high school students. Practitioners rated the e-module as highly effective and contextually relevant for classroom use. The e-module serves as a self-learning resource that strengthens students' understanding before playing the game. Interactive components and evaluation exercises allow students to independently measure their achievements while increasing their motivation to learn through integration with technology-based applications. It can be concluded that the SIGAME e-module is “Very Adequate” for use in the next development stage, namely testing its practicality and implementing learning in schools, as an independent learning resource that supports mastery of the concept of classifying living things.